Pengembangan Media Pembelajaran Interaktif menggunakan Aplikasi Construct pada Elemen Komponen Elektronika Aktif dan Pasif - Syaputra, Rizky; Efrizon, Efrizon (TSAQOFAH, 2025)
This study discusses the development of interactive learning media using the Construct application for the topic of active and passive electronic components at SMK Negeri 5 Padang. The research aims to produce interactive learning media that can enhance student engagement and to evaluate the feasibility of the media. The Research and Development (R&D) method was employed, utilizing the 4D development model, which includes the stages of Define, Design, Development, and Dissemination. Data collection was conducted through questionnaires using a Likert scale to measure users’ attitudes, opinions, and perceptions. Validation by media experts yielded a score of 83.75%, categorized as very valid; content expert validation scored 77.77%, categorized as valid; and practical testing by users (students) achieved 81.99%, categorized as highly practical. In conclusion, the interactive learning media based on the Construct application for active and passive electronic components is feasible for use and effective in enhancing student engagement at SMK Negeri 5 Padang.